(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
This article deals with part of the trajectory of the brazilian art educator Joana Lopes, especially the practical propositions focused on the dramatic play. Through comments to some of his scenic works and recorded reflections on his work, some aspects of his authorial proposal of research in theather-education are discussed. More than revealing traces that can be identified as dated and surpassed in an artistic work, it is interesting to highlight the precursor and investigative character of an art-educator that continues producing and reflecting on multiple approaches to the dramatic play.